Social attraction to a predatory black hole: A natural ecological trap for lobsters - Mark J. Butler; Donald C. Behringer; Jason Schratwieser (Proceedings of the National Academy of Sciences, 2026)
Ecological traps occur when animals erroneously choose habitats that lower their fitness, drawn by cues that are adaptive in most instances, but not all. Most ecological traps result from anthropogenic changes that make habitats less beneficial, yet still attractive to unsuspecting animals. Naturally occurring ecological traps are rare, persisting despite their drain on population sustainability. We found an unusual natural ecological trap whereby social juvenile Caribbean spiny lobsters ( Panulirus argus ) are drawn to solution hole dens by the scent of larger conspecifics dwelling there, but where predatory red grouper ( Epinephelus morio ) also lurk. Although lobsters are sensitive to odors from food, healthy and diseased conspecifics, and other predators such as octopus, our experiments revealed that lobsters cannot detect the scent of groupers. As a consequence, mortality of small juvenile lobsters was 30% higher near solution holes occupied by grouper, as compared to larger lobsters that are invulnerable to the gape-limited grouper predator. By preying on small lobsters, grouper negatively skewed lobster size distributions up to 16 m away from the solution hole lair that they patrol. Our results provide one of the clearest examples of a natural ecological trap, in which the normally advantageous social cue of large conspecifics lures young lobsters to what is a predatory death trap. Although anthropogenically driven traps are an evolutionarily new and destabilizing force for animal populations, natural ecological traps like this one are ecological oddities whose effects on populations can be locally intense, yet persist through time.